IPad versus traditional tools in art and design: A complementary association. (11th March 2016) - Souleles, Nicos
Abstract: There is continuous debate on the role of digital media tools in art and design Higher Education, and in particular their potential contribution towards teaching and learning. The related literature indicates that there is a dichotomy between digital and traditional tools. This study investigates the views of a cohort of art and design students who undertook a specific instructional task, but instead of using paper and pencil, they used iPads. It is claimed that this computer tablet has considerable potential to enhance teaching and learning, and this study sought to investigate this claim. Inductive qualitative content analysis was used to analyse the interviews provided by 32 ( n = 32) students. Based on the categories that emerged from the analysis of interviews, and within the parameters of this study, the main inference is that the relationship between digital and traditional tools can be better understood as complementary rather than as a dichotomy. A video abstract of this article can be viewed at https://youtu.be/Ws‐nTXb_BrY